Altitudinal Variation in Soil Fungal Community Associated with Alpine Potentilla fruticosa Shrublands in the Eastern Qinghai–Tibet Plateau - Lele Xie; Yushou Ma; Yanlong Wang; Yuan Ma; Yu Liu (Agronomy, 2025)
Soil fungi serve as key mediators of belowground ecological processes; however, the altitudinal distribution patterns and their driving mechanisms of soil fungal communities in alpine shrubland ecosystems remain poorly understood. In this study, soil samples were collected from Potentilla fruticosa shrubs at different altitudes, and their physical and chemical properties were determined. Illumina MiSeq sequencing technology was used to study the characteristics of soil fungal communities at different altitudes (3400, 3700, 4000, and 4300 m), and the driving factors affecting the composition of soil fungal communities were found through variance analysis and redundancy analysis. With the increase in altitude, species diversity decreased while total phosphorus and available phosphorus increased. Compared with 3400 m, the diversity index (Sobs, Chao1, and ACE index) of the soil fungal community at 4000 m is the highest, and that at 4300 m is the lowest. NMDS analysis showed that there were significant differences among soil fungal community structures at different altitudes. Redundancy analysis (RDA) indicated that available potassium, available phosphorus, and the Shannon–Wiener diversity index were the primary factors influencing the variation in soil fungal communities along the elevation gradient. Furthermore, the impact of soil physical and chemical properties on soil fungal communities was found to be more pronounced than that of plant characteristics. Network analysis shows that the network complexity is the highest at 4300 m above sea level. These studies provide a new perspective and basis for understanding the distribution pattern of soil fungi in the rhizosphere Potentilla fruticosa in the eastern Qinghai–Tibet Plateau.